\frac{ \sqrt{3 }  +  \sqrt{2} }{ \sqrt{3} -  \sqrt{2}  } = a + b \sqrt{6}

Question

 \frac{ \sqrt{3 }  +  \sqrt{2} }{ \sqrt{3} -  \sqrt{2}  } = a + b \sqrt{6}

in progress 0
Ruby 5 months 2021-07-18T22:36:31+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-18T22:38:21+00:00

    Answer:

    a = 5 and b = 2

    Step-by-step explanation:

    (√3+√2)/(√3-√2) × (√3+√2)/(√3+√2)

    (√3+√2)²/(√3-√2)(√3+√2)

    (√3)²+(√2)²+2(√3)(√2)/(√3)²-(√2)²

    3+2+2√6/3-2

    5+2√6

    comparing with a+b√6,

    5+2√6 = a+b√6

    we get a = 5 and b = 2

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )